Application of response surface methodology for the optimization of hydro-distillation extraction of Pistacia lentiscus L. essential oil - Taoufik Haloui, Abdellah Farah, Sara Lebrazi, Mouhcine Fadil, Aziz Belrhiti Alaoui (Journal of Applied Pharmaceutical Science, 2018)
The evaluation of the optimum conditions for extraction of Pistacia lentiscus essential oil by hydro-distillation process required a design of experiments (DOE). The selected factors of composite design are the time of hydro-distillation and the ratio of the plant material and water. Response surface methodology was used to evaluate the effects of pro¬cessing parameters and the extraction yields varied in the range of 0.4-0.58% (w/w) under different conditions. This study proved high efficiency of the response surface methodology application to optimize the operational parameters influencing the yield of essential oil extracted by hydro-distillation process of Pistcia lentiscus L. leaves To get a better essential oil yield with the most economic operating parameters.
Keywords: Pistacia lentiscus, essential oil, hydro-distillation, composite design, response surface